Internally Displaced Persons in Nigeria: Review of Empirical Studies - Okon, Emmanuel Okokondem (American International Journal of Social Science Research, 2018)
The purpose of this paper is to review empirical studies on the issue of internally displaced persons in Nigeria. The aim is to document the different ways and methods in which researchers have approached this phenomenon in the past and to identify gaps. Thus lessons drawn will help in the effort ofcurbing the menace of this phenomenon.The paper started by giving a literature on the current global trend of displacement followed by the current situation of displacement in Nigeria. Thereafter, a general search was conducted in different online database sources such as Google Scholars, mamma.com, Springer Link, Wiley, Askme.com,Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST, etc., to find out studies that have been carried on internally displaced persons in Nigeria.The empirical literature review shows that studies conducted in Nigeria on internally displacement covered among others issues such: causes and factors which induce internal displacement, internal intervention for IDPs, Psychosocial challenges of IDPs, provision of education for IDPs,inclusive electoral process for IDPs in Nigeria. However, no study has been conducted to analyze how the arrival of displaced individuals affects the provision of public goods of local residents. This unexplored impact may have important implications for the welfare of receiving locations given the large magnitude of displacement experienced in some parts of Nigeria.Studies have also not been conducted to examine how those displaced are affected in terms of employment and welfare losses. Most importantly, research should be geared towards mitigating this phenomenon.